Modeling of thermal cycles and microstructural analysis of pipeline steels processed by friction stir processing - Avila, J. A. [UNESP] (2018)
During friction stir welding or processing (FSP), temperature and deformation have influence on the final microstructure and mechanical properties. Studying microstructures before and after welding might help interpreting mechanical and corrosion resistance; however, microstructural evolution during the process remains unknown. In this study, a FSP model of pipeline steel plates was developed. Thermocouples were inserted in different positions and temperature cycles were collected during FSP. The collected data was used to complete the numerical model based on computational fluid dynamics (CFD). The CFD model simulated the material flow and heat transfer in FSP considering the material as a fluid. The standard error between the peak temperatures of the simulation and experimental results was below 1%. The model allowed correlating peak temperatures and cooling rates to the obtained microstructures after FSP. Numerical results showed that peak temperatures and dwell times in the stir zone were high enough to cause grain coarsening. This observation was demonstrated upon prior-austenite grain size measurements.